2015
DOI: 10.1159/000369524
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Surgical Treatment, and Long-Term Outcome in Pediatric Patients with Moyamoya Disease in China

Abstract: Background: There was few detailed demographic and clinical data about Chinese patients with moyamoya disease. Here we describe the clinical features, surgical treatment, and long-term outcome of pediatric patients with moyamoya disease at a single institution in China. Methods: Our cohort included 288 pediatric patients with moyamoya disease. The demographic and clinical characteristics were obtained by retrospective chart review and long-term outcome was evaluated using the stroke status. Univariate and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 43 publications
3
57
2
Order By: Relevance
“…5,6,11,14,32,34 Preoperative cerebral infarction, younger age at onset, involvement of the PCA, intentional hypotension, high Suzuki stage, and postoperative ischemic events have been observed to correlate with postoperative complications and outcomes. According to the multivariate logistic regression analyses, our study showed that PCA involvement in both groups with no statistically significant differences preoperatively together with the late postoperative stroke was associated with unfavorable clinical outcomes, which was similar to the previous results observed in our center.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,11,14,32,34 Preoperative cerebral infarction, younger age at onset, involvement of the PCA, intentional hypotension, high Suzuki stage, and postoperative ischemic events have been observed to correlate with postoperative complications and outcomes. According to the multivariate logistic regression analyses, our study showed that PCA involvement in both groups with no statistically significant differences preoperatively together with the late postoperative stroke was associated with unfavorable clinical outcomes, which was similar to the previous results observed in our center.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…27 Surgical revascularizations such as direct, indirect, or combined anastomosis have been proven to be effective in improving decreased cerebral circulation and clinical signs. 25 Encephaloduroarteriosynangiosis (EDAS) is an indirect revascularization procedure that has been shown to be beneficial for pediatric 6,12,22 and adult populations. 2,5,7 The results of revascularization due to EDAS are associated with some factors, including age, complications, and other unknown factors.…”
mentioning
confidence: 99%
“…Children with MMD usually present with ischemic attacks, whereas adults may have either ischemic or hemorrhagic events [13,14] . Other manifestations include migraine-like headaches and movement disorders.…”
Section: Introductionmentioning
confidence: 99%
“…We included studies meeting the following criteria: [1] Observational studies describing patients with the diagnosis of MMD according to the diagnosis and treatment guideline (31) [2] Patients that underwent revascularization surgery either by direct bypass, indirect bypass or combined bypass [3] With an exact definition of good functional outcome [4] Recording the number of patients with good outcome or the rate [5] With follow-up time of at least 6 months.…”
Section: Study Selectionmentioning
confidence: 99%